C2 Vertebra: An Enigma for Young Spine/Neurosurgeons - Garg, Mayank; Sharma, Raghavendra K.; Janu, Vikas; Agrawal, Mohit; Jha, Ashutosh; Khera, Pushpinder; Jha, Deepak K. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Instrumentation of C2 vertebra is considered the most difficult for young neurosurgeons and trainees due to its complex anatomical structures, variety of surgical approaches and techniques, and proximity to important neurovascular structures. Key points from a surgical perspective for midline posterior approach is described in the era of neuroradiological advancements.Method Computed tomography angiographies (CTAs) of a total of 92 patients were evaluated with special attention to the key findings for insertion of screws for craniovertebral junction (CVJ) fixations. All these patients were operated though midline posterior approach in past 4 years.Results CTAs included various CVJ disorders, which included traumatic (n = 14), congenital (n = 55), and rheumatoid arthritis (n = 2) patients. Established landmarks for screw insertion sites do not prove safe for congenital anomalous CVJ conditions. Instead of highlighting screw insertion entry points, part of the corridor, which is relevant, should be stressed up on.Conclusion Midpoint of portion of bone segment medial to vertebral artery foramen should be the focus, which is important for pars interarticularis (and transarticular) and pedicle screws. A laminar screw should cross the midpoint of the lamina on each side.
Keywords: C2 vertebra; basilar invagination; congenital anomaly; craniovertebral junction; occipitocervical fixation